2011
DOI: 10.1007/s11368-011-0400-1
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual model and sensitivity analysis for simulating the extraction kinetics of soil washing

Abstract: Purpose Most previous studies focused on the metal extraction efficiency of chelant-enhanced soil washing under various operational conditions; however, one of the keys to cost-effective field application is to maintain a high throughput rate (i.e., short washing time) while achieving the treatment objectives. Therefore, this study presented a conceptual model for simulating the kinetic extraction of heavy metals and evaluated its sensitivity analysis to the predetermined parameter values in five soils with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In their study, equilibrium was reached within 6 h with most soils. Tsang et al (2011) found that heavy metals (Pb, Zn, Cu) removal from soil with EDTA followed 1st order kinetics; however, this proceeded in two phases, rapid extraction during the first few hours followed by gradual extraction.…”
Section: Kinetics Of Metal Removal With Hamentioning
confidence: 99%
“…In their study, equilibrium was reached within 6 h with most soils. Tsang et al (2011) found that heavy metals (Pb, Zn, Cu) removal from soil with EDTA followed 1st order kinetics; however, this proceeded in two phases, rapid extraction during the first few hours followed by gradual extraction.…”
Section: Kinetics Of Metal Removal With Hamentioning
confidence: 99%
“…The chelation process works on the concept of coordinative incorporation of a metal ion into a heterocyclic ring structure in which monodentate ligands are replaced by multidentate ones to form a metal–ligand complex . The chelating agent-assisted metal extraction process takes place into two steps: formation of metal–ligand complexes on WEEE surfaces and then kinetic detachment of the complex from WEEE into aqueous solution to maximize the thermodynamic stability of the complex. Mass transfer of liquid extractant from the solid–liquid interface to the inner zone of the WEEE particles and then mass transfer of the metal–ligand complex from the interior of WEEE to bulk of the liquid extractant exclusively depend upon external and internal diffusion mechanisms. External diffusion involves rapid extraction of metals from superficial sites of the solid surface, whereas internal diffusion suggests extraction of metals present on internal sites of particles.…”
Section: Introductionmentioning
confidence: 99%
“…Chelating agent assisted metal extraction process starts with the formation of metal-ligand complexes on catalyst surfaces and then kinetic detachment of the complex takes place from catalyst surfaces into the solution (i.e. dissociation) to maximize the thermodynamic stability of the complex [15,18,[22][23][24][25]. The process commences with the mass transfer of liquid extractant from solid-liquid interface to inner zone of the catalyst particles and then mass transfer of metalligand complex from interior of catalyst particles to bulk of the liquid extractant.…”
Section: Introductionmentioning
confidence: 99%